Design, synthesis, in vitro, and in silico studies of novel diarylimidazole-1, 2, 3-triazole hybrids as potent α-glucosidase inhibitors. Issue 23 (1st December 2019) - Saeedi, Mina; Mohammadi-Khanaposhtani, Maryam; Asgari, Mohammad Sadegh; Eghbalnejad, Nafiseh; Imanparast, Somaye; Faramarzi, Mohammad Ali; Larijani, Bagher; Mahdavi, Mohammad; Akbarzadeh, Tahmineh
Graphical abstract: Highlights: New derivatives of diarylimidazole-1, 2, 3-triazole 7a-p were designed and synthesized. All compounds were evaluated for their in vitro α-glucosidase inhibitory activity. All compounds were found to be potent inhibitors in the range of IC50 = 90.4–246.7 µM comparing with acarbose (IC50 = 750.0 µM) as the standard drug. Among the synthesized compounds, compounds 7b, 7c, and 7e were approximately 8 times more potent than acarbose. Abstract: In this work, new derivatives of diarylimidazole-1, 2, 3-triazole 7a-p were designed, synthesized, and evaluated for their in vitro α-glucosidase inhibitory activity. All compounds showed potent inhibitory activity in the range of IC50 = 90.4–246.7 µM comparing with acarbose as the standard drug (IC50 = 750.0 µM). Among the synthesized compounds, compounds 7b, 7c, and 7e were approximately 8 times more potent than acarbose. The kinetic study of those compounds indicated that they acted as the competitive inhibitors of α-glucosidase. Molecular docking studies were also carried out for compounds 7b, 7c, and 7e using modeled α-glucosidase to find the interaction modes responsible for the desired inhibitory activity.